Tissue Structure of Pangasianodon hypophthalmus Fed on Cosmos caudatus-Enriched Pellets and Reared in Saline Media - Difa Syafwali; Windarti Windarti; Efawani Efawani (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Cosmos caudatus is known as an herb that may improve fish health in general. However, the effects of this herb provision on the fish tissue structure have never been studied. To determine any changes in fish tissue provided with C. caudatus-enriched pellets, a study was conducted in June - August 2024. A CRD with 4 treatments: T0 (control), T1 (10 g/kg), T2 (15 g/kg), and T3 (20 g/kg), and 3 replications per treatment was applied. Commercial fish feed pellets were mixed with C. caudatus powder, and this feed was given to the experimental fish 3 times/day, at satiation. The fish was reared in saline media (5 ppt) for 60 days. By the end of the experiment, the tissue was removed and processed for histological study (formalin-fixed, alcohol series processed, 5mm sliced, HE-stained). Results showed that the provision of C. caudatus-enriched pellets does not affect the tissue structure of the fish in general, as the tissue structure was almost normal. However, abnormalities were observed in several fish, including the control fish, including hyperplasia and hemorrhage in the gills, glomerular damage and hemorrhage in kidney tissue, and hepatocyte damage in the liver. As the control fish that were not fed C. caudatus showed abnormalities in their tissues, it is predicted that the provision of C. caudatus may not cause the damage; instead, it may be related to other factors, such as water salinity. T1 (10 g/kg feed) had the highest survival rate at 96.66%. Based on the data provided, it can be concluded that the provision of C. caudatus-enriched pellets does not negatively affect the fish's tissue structure.